DAMPAK PANDEMI COVID-19 TERHADAP PROSES PEMBELAJARAN MATEMATIKA PADA SISWA SEKOLAH DASAR - Ramadani Nasution; Eva Monika Safitri Lubis (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2022)
AbstractStudents in elementary schools enter the level of concrete operational, so that, they need a media to understanding the various existing concepts of learning. Learning mathematics requires concrete objects and explanations from the teacher. Due to the COVID-19 pandemic, learning has be completely by online, as well as math lessons. The purpose of this study was to see the impact of the COVID-19 pandemic on the mathematics learning process for teachers, students and parents. This research method is a qualitative method and literature study. The results of the study show that the impact of the COVID-19 pandemic on teachers, students and parents is very large. The lack of knowledge about the use of technology, some parents who do not receive an education and a large enough expenditure are obstacles for the mathematics learning process. Keywords: Pandemic, Covid-19, Mathematics Learning. AbstrakSiswa di Sekolah Dasar memasuki tahap operasional konkrit, seingga memerlukan suatu media untuk dapat menangkap berbagai konsep yang ada. Pembelajaran matematika memerlukan benda konkrit dan penjelasan dari guru. Adanya pandemi covid-19 menjadikan pembelajaran harus serba online, tidak terkecuali matematika. Tujuan dari penelitian ini adalah untuk melihat dampak pandemi covid 19 terhadap proes pembelajaran matematika bagi guru, siswa dan orangtua. Metode penelitian ini adalah metode kualitatif dan studi kepustakaan. Hasil penelitian menunjukan bahwa dampak pandemi covid19 terhadap guru, siswa dan orang tua sangat besar. Minimnya pengetahuan mengenai peggunaan teknologi, beberapa orang tua yang tidak mengenyam pendidikan dan pengeluaran yang cukup besar menjadi kendala terhadap proses pembelajaran matematika. Kata Kunci: Pandemi Covid-19, Pembelajaran Matematika